1976
DOI: 10.1139/o76-117
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic synthesis of C40 carotenes by cell-free preparation from Halobacterium cutirubrum

Abstract: [14C]Mevalonate or (14C)isopentenyl pyrophosphate was found to be converted to transphytoene, trans-phytofluene, lycopene, and beta-carotene by a cell-free 270 000 X g supernatant fraction prepared from Halobacterium cutirubrum cells that were broken by manual grinding with glass beads. Incubations were done under N2 in the dark at 37 degrees C in 4 M NaCl in presence of FAD, NADP, and MgCl2; ATP was also added when mevalonate was the substrate. This system was also capable of converting trans-(14C)phytoene to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…An early in vitro work on C 40 carotene synthesis in Halobacterium cutirubrum also showed that isoprenoids are synthesized from MVA via IPP, even though carotenes are not components of polar lipids (57). In vitro assays of enzyme activities of the pathway supported the conclusion led by the in vivo evidence.…”
Section: Mva Pathway From Acetyl-coa To Dmappmentioning
confidence: 82%
“…An early in vitro work on C 40 carotene synthesis in Halobacterium cutirubrum also showed that isoprenoids are synthesized from MVA via IPP, even though carotenes are not components of polar lipids (57). In vitro assays of enzyme activities of the pathway supported the conclusion led by the in vivo evidence.…”
Section: Mva Pathway From Acetyl-coa To Dmappmentioning
confidence: 82%
“…This pathway was based on the in vitro reconstitution of ␤-carotene formation from mevalonate (32) and on the accumulation of C 40 -isoprenoid intermediates in colorless mutant strains that lacked ␤-carotene and retinal (33). However, direct biochemical or genetic evidence for the conversion of ␤-carotene to retinal has not been obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Early steps in the pathway are shared with the biosynthesis of phytanyl, the hydrophobic portion of the polar lipids that make up archaeal cell membranes, with the 20-carbon geranylgeranyl diphosphate (GGPP) being the last shared intermediate (7). In the retinal biosynthetic pathway, two GGPP molecules condense to form the 40-carbon carotenoid phytoene, which undergoes a series of desaturation reactions to form the red carotenoid lycopene (23). For retinal synthesis, lycopene cyclizes to form ␤-carotene, which is cleaved to form the 20-carbon retinal cofactor (23,42).…”
mentioning
confidence: 99%
“…In the retinal biosynthetic pathway, two GGPP molecules condense to form the 40-carbon carotenoid phytoene, which undergoes a series of desaturation reactions to form the red carotenoid lycopene (23). For retinal synthesis, lycopene cyclizes to form ␤-carotene, which is cleaved to form the 20-carbon retinal cofactor (23,42). Alternatively, lycopene may be used as a precursor for bacterioruberins: tetrahydrobisanhydrobacterioruberin, bisanhydrobacterioruberin, and bacterioruberin (22,24).…”
mentioning
confidence: 99%